N-pentane originated protonic acid sites over zinc promoted HZSM-5 - Musthofa, Malik (2009)
The formation of protonic acid sites from hydrogen and n-pentane over Zn/HZSM-5 was evidenced by pyridine adsorption IR spectroscopy. The results showed that protonic acid sites were formed by heat treatment of Zn/HZSM-5 in the presence of molecular hydrogen which started at room temperature with a concomitant elimination of Lewis acid sites. Removal of molecular hydrogen decreased the protonic acid sites and restored the Lewis acid sites to its original intensity at 573 K. These phenomena are consistent with the concept of ‘molecular hydrogen-originated protonic acid sites’ in which the process is initiated by dissociation of hydrogen molecules to hydrogen atoms, spilling over onto the HZSM-5 and followed by surface diffusion. Then hydrogen atom converts into a proton by releasing electron to Lewis acid site. The formation of protonic acid sites on Zn/HZSM-5 induced by molecular hydrogen is a reversible process. The protonic acid sites were also formed from n-pentane on Zn/HZSM-5. Lewis acid sites were converted to protonic acid sites when the sample was heated in n-pentane, and the formed protonic acid sites were subsequently eliminated by removal of n-pentane with a restoration of Lewis acid sites. These are essentially the same as a formation of protonic acid sites from molecular hydrogen. It is plausible that the formation of protonic acid site was initiated by dissociation of n-pentane to form hydrogen atom and certain molecule. Then, the hydrogen atom spills over onto the HZSM-5 followed by surface diffusion to form protonic acid sites by releasing electron to the Lewis acid sites. The formed protonic acid sites which act as active sites played significant role in the reactions of n-pentane.